Smartwatch-Based Blood Pressure Measurement Demonstrates Insufficient Accuracy - Falter, Maarten; Scherrenberg, Martijn; Driesen, Karen; Pieters, Zoë; Kaihara, Toshiki; Xu, Linqi; Caiani, Enrico Gianluca; Castiglioni, Paolo; Faini, Andrea; Parati, Gianfranco; Dendale, Paul (Frontiers in Cardiovascular Medicine, 2022)
Background Novel smartwatch-based cuffless blood pressure (BP) measuring devices are coming to market and receive FDA and CE labels. These devices are often insufficiently validated for clinical use. This study aims to investigate a recently CE-cleared smartwatch using cuffless BP measurement in a population with normotensive and hypertensive individuals scheduled for 24-hour BP measurement. Methods Patients that were scheduled for 24-hour ambulatory blood pressure monitoring (ABPM) were recruited and received an additional Samsung Galaxy Watch Active 2 smartwatch for simultaneous BP measurement on their opposite arm. After calibration, patients were asked to measure as much as possible in a 24-hour period. Manual activation of the smartwatch is necessary to measure the BP. Accuracy was calculated using sensitivity, specificity, positive and negative predictive values and ROC curves. Bland-Altman method and Taffé methods were used for bias and precision assessment. BP variability was calculated using average real variability and standard deviation. Results Forty patients were included. Bland-Altman and Taffé methods demonstrated a proportional bias, in which low systolic BPs are overestimated, and high BPs are underestimated. Diastolic BPs were all overestimated, with increasing bias towards lower BPs. Sensitivity and specificity for detecting systolic and/or diastolic hypertension were 83% and 41% respectively. ROC curves demonstrate an area under the curve (AUC) of 0.78 for systolic hypertension and of 0.93 for diastolic hypertension. BP variability was systematically higher in the ABPM measurements compared to the smartwatch measurements. Conclusions This study demonstrates that the BP measurements by the Samsung Galaxy Watch Active 2 show a systematic bias towards a calibration point, overestimating low BPs and underestimating high BPs, when investigated in both normotensive and hypertensive patients. Standards for traditional non-invasive sphygmomanometers are not met, but these standards are not fully applicable to cuffless devices, emphasizing the urgent need for new standards for cuffless devices. The smartwatch-based BP measurement is not yet ready for clinical usage. However, when used complementary to a cuff-based BP monitor, BP measurements might be of value. Future studies are needed to further validate wearable devices, and also to demonstrate new possibilities of non-invasive, high-frequency BP monitoring.